Biochemical markers for prolongation of the acute stress of triclosan in the early life stages of four food fishes. (May 2020) - Dar, Owias Iqbal; Sharma, Sunil; Singh, Kirpal; Sharma, Anket; Bhardwaj, Renu; Kaur, Arvinder
Abstract: In the present study, embryos of four food fishes viz. Cyprinus carpio, Ctenopharyngodon idella, Labeo rohita and Cirrhinus mrigala were given acute (96 h) exposure to their respective LC0, LC10 and LC30 (causing 0, 10 and 30% mortality, respectively) concentrations of triclosan [TCS, 5-chloro-2-(2, 4-dichlorophenoxy) phenol], a broad spectrum biocide. Bioaccumulation, contents of protein, non-enzymatic antioxidants (GSH and GSSG), MDA (lipid peroxidation product) and organic acids (fumarate, succinate, malate and citrate) along with the activities of AChE (neurological enzyme), GST (detoxification enzyme) and three metabolic enzymes (LDH, AST and ALT) were estimated after 48 and 96 h exposure and 10 days post exposure. Around 1/10 of the TCS in water got accumulated in the hatchlings after 96 h, increase over 48 h values was maximum at LC0 (+195.30,  +143.23 and + 140.75%) but minimum at LC30 (+89.62,  +84.26 and + 126.72%) for C. idella, L. rohita and C. mrigala, respectively. In C. carpio, TCS got accumulated only at LC30 after 48 h but at all the concentrations after 96 h exposure. Contents of protein, GSH, GSSG and activity of AChE decreased but activities of GSH, LDH, AST and ALT and contents of MDA and organic acids increased concentration dependently in all the fishes. TCS declined by 85–90% but its toxic effects on biomolecules prolonged till the end of the recovery period. Such acute exposures are accidental but there is a need to evaluate biomarkers for prolongation of the stress of small concentrations especially LC0 and LC10 (causing negligible mortality) of lipophilic pollutants like TCS. Highlights: Triclosan is highly toxic to the early life stages of Cyprinus carpio, Ctenopharyngodon idella, Labeo rohita and Cirrhinus mrigala. 10% of triclosan in water got accumulated in the embryos/hatchlings. 10 days post exposure, TCS declined by 85–90% in the tissues of all the species. Triclosan caused species specific alteration in the biochemical parameters. The stress of 96 h exposure on biomolecules prolonged till 10 days of recovery period.